PENURUNAN SUBSIDI ENERGI DAN KEMISKINAN DI INDONESIA - Puja Delvia; Aliasuddin Aliasuddin (Fakultas Ekonomi dan Bisnis UNSYIAH, 2020)
AbstractThis study aims to analyze the reduction in energy subsidies and poverty in Indonesia. The method used in this study is the Ordinary Least Square (OLS) model. The data used are annual data the period of 1998-2018. The variables used are government spending, energy subsidies, inflation, and the amount of poverty that comes from the Central Statistics Agency (BPS). The results indicated that there was a positive effect between energy subsidies and poverty but was not significant. The reduction in energy subsidies does not directly affect poverty, due to low use of energy within the poor. The research implies that policy decision makers to reduce energy subsidies do not make a difference between the period before and after, this indicates that all estimation periods did not change significantly.Keywords: Government spending, energy subsidies, inflation, poverty, OLS